Biologia de meteorus sp hymenoptera braconidae parasitoide de larvas del carterpilar del banano - Noblecilla Paccha, Carlos (2008)
In sequential generations of Caterpilar, monitored in a lot "pockets" of the Hda Celia Maria CA from June to November de/07, is developing the study of the life cycle of Meteorus sp with the following objectives: 1.-Studying the life cycle of a species of Meteorus sp parasitoid of the last larval stages of Caterpilar banana from pupae collected.2.-To determine the biological parameters relating to the state of egg, larva, pupa and adult, leading to know the potential of parasitism. 3.-Develop a new collection of parasitoids to the museum of Entomology CIAP. The lab work conducted in Hda Celia Maria CA, from pupae collected in the field and confined in crates emergency adult, with the purpose of knowing in advance the behavior of adults; after the preliminary observations and the manipulation of biological material to acquire the skill in handling and dissection of the larvae final study began with generations of the rainy season to intensify work in the sixth to eighth. It used small cameras parasitism larvae conical shape trunk-12 cm base 10cm ceiling and 11 cm high with the top ventilated through a fine cloth of organza.The interior was placed a group of 5 larvae from 1 to 2 cm in size with circular segments of banana leaves for its food, at 2, 3 and 4 days were withdrawn in order to obtain eggs and dissected, the same as placed in porta concave objects for observation by staining fushina acid. In the field intensity was recorded registrando parasitism by the number of pupae parasitized larvae.The total life cycle takes about 24 to 27 days, spread over 15 days for Phases egg, until the emergence of the third larval stage, the formation of the cocoon lasted from 4 to 6 hours. Pupa, 6 days and the adult lives 4 to 5 days. The adults emerge at night and the ratio of male to female 10-7.